Quantification of systolic anterior motion of the mitral valve to predict left ventricular outflow tract obstruction in patients with hypertrophic cardiomyopathy. (3rd October 2022) - Verheyen, N; Batzner, A; Zach, D; Zirlik, A; Gerull, B; Stoerk, S; Maack, C; Seggewiss, H; Morbach, C
Abstract: Background: In patients with hypertrophic cardiomyopathy (HCM), left ventricular outflow tract obstruction (LVOTO) is associated with an increased risk of heart failure and death (1). It is typically caused by dynamic systolic anterior motion (SAM) of the mitral valve leaflet. SAM can be categorized by echocardiography but diagnostic accuracy is limited by high inter-observer variability. Purpose: To investigate the accuracy of echocardiographic parameters quantifying systolic motion of the mitral valve leaflets to identify LVOTO in patients with HCM. Methods: We present a cross-sectional analysis of the HyperCard Registry, a prospective single-center cohort study enrolling consecutive patients with suspected or confirmed HCM. For the present analysis, patients with confirmed HCM and a valid standardized transthoracic echocardiographic were included. LVOT gradients were measured at rest and during Valsalva maneuver using continuous wave Doppler. In patients with clinical suspicion of dynamic LVOTO, further provocation maneuvers were conducted. LVOTO was defined as a maximal peak LVOT gradient ≥30 mmHg. Parameters quantifying systolic motion of the mitral valve were measured in parasternal and apical views, both at early and late systole, by an investigator blinded to individual patient characteristics. SAM was visually assessed and categorized into grade 0 (no SAM), I (leaflet motion towards LVOT), II (late systolic septal contact), and III (early systolic septal contact). Results: We analyzed 142 patients (59±13 years, 42% women). LVOTO was present in 68 (48%) patients of whom 30 (21% of all) exhibited LVOTO at rest, and 38 (27% of all) had LVOTO only during provocation maneuvers (ie. dynamic LVOTO). SAM was present in 86 patients (60%) and had a sensivitiy, specificity and PPV of LVOTO of 91%, 69% and 73%, respectively (table). The late-systolic distance between mitral leaflet tip and anterior septum (TISls) measured in apical 3-chamber view was best associated with the degree of SAM (F=123, P<0.001), and with peak LVOT gradient (at rest: Pearson r=−0.817; during Valsalva maneuver: r=−0.816, both P<0.001). In ROC analyses (figure), the AUC of TISls for identification of LVOTO and dynamic LVOTO were 0.914 (95% CI 0.868–0.959) and 0.857 (0.786–0.927), respectively. TISls ≤14 mm had a 97% sensitivity for LVOTO and of 94% for dynamic LVOTO. TISls ≤9 mm showed specificity and PPV of 95% and 92% for LVOTO, and 94% and 83% for dynamic LVOTO, respectively. Conclusions: Quantification of SAM by TISls showed high diagnostic accuracy in identifying HCM patients with LVOTO. Prospective studies are needed to assess the incremental benefit of this novel parameter in the diagnostic work-up of HCM patients. Funding Acknowledgement: Type of funding sources: None.